Contamination of Salmonella sp. Bacteria on Broiler Chicken Meat - Dharwin Siswantoro; Rizqi Annas Mubarok; Anang Febri Prasetyo; Rosa Tri Hertamawati; Satria Budi Kusuma (UNIVERSITAS ISLAM LAMONGAN, 2022)
This study aims to identify the contamination of Salmonella sp. on broiler chicken circulating in traditional markets in Jember Regency. This study uses a survey method with purposive sampling technique. Observation of Salmonella sp. was done through carrying out inoculation of Salmonella sp. on SSA media, identifying KOH and gram staining on Salmonella sp., and doing observation using a microscope. The parameters of this study were testing the content of Salmonella sp. on broiler chicken meat and counting the number of colonies of Salmonella sp. Data analysis used in this study were the binomial test and descriptive analysis. The test results for Salmonella sp. in the sample of meat sold at Traditional Markets in Jember Regency was above 0 cfu/g. This meant that there was contamination of Salmonella sp. on the observed meat samples, while SNI (3924-2009) requires that consumption of chicken meat products must be negative from contamination by Salmonella sp. The results of the binomial test showed a significant difference (P <0.05) against SNI (3924-2009). Contamination value of Salmonella sp. The highest contamination was found in sample (P8) which was 7.22 x 106 bacteria. Meanwhile, the lowest contamination was found in the sample (P10) which was 3.02 x 104 bacteria. Based on the results of this study, it can be concluded that there is contamination of Salmonella sp. on broiler chicken circulating in traditional markets in Jember Regency. This is not in accordance with SNI (3924-2009).